"Doomed to die" - Nigh, William, 1881-1955; Karloff, Boris, 1887-1969; Monogram Pictures Corporation; Cinetel Films ([Los Angeles, CA] : Monogram Pictures Corporation, 1940)
A luxury liner carrying 400 passengers and a contraband cargo of Chinese bonds worth over a million dollars is destroyed by fire. Then the president of the shipping firm is mysteriously murdered during a heated argument with his daughter's fiance, who is the son of a rival shipping magnate. The detective (Boris Karloff as a Chinese sleuth) is wounded in the arm by an unknown assailant while tracking down a clue in Chinatown. Can he uncover the real culprit?
Based on the 'James Lee Wong' series in Collier's Magazine written by Hugh Wiley.
Boris Karloff, Marjorie Reynolds, Grant Withers, William Stelling, Catherine Craig, Guy Usher, Hnery Brandon, Melvin Lang, Wilbur Mack, Kenneth Harlan, Richard Loo.
Cinematographer, Harry Neumann; editor, Robert Golden; musical director, Edward Kay.
In English or Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 21, 2015)
Keywords: Wong, Mr. (Fictitious character) -- Drama; Shipping -- Drama; Murder -- Investigation -- Drama; Feature films; Internet videos; Streaming video